Cenozoic synthem stratigraphic architecture of the SE Brazilian shelf and its global eustatic context: evidence from the Pelotas Basin (offshore Brazil) - de Santana dos Anjos Zerfass, Geise; Ruban, Dmitry A.; Chemale Jr., Farid; Zerfass, Henrique (Bogucki Wydawnictwo Naukowe, 2013)
The Pelotas Basin, located on the SE Brazilian shelf, has evolved since the Aptian. Stratigraphical data from the basin can be used for delineation of the unconformity-bounded units (synthems) on the shelf, which is a first step towards a full understanding of its stratigraphic architecture, evolution, and hydrocarbon potential. Hiatuses in the Cenozoic succession of the Pelotas Basin are established with both biostratigraphic (planktonic foraminifers and calcareous nannofossils) and isotopic (87Sr/86Sr) data. The seven recognised hiatuses are dated respectively as (1) Palaeocene (Danian- Thanetian), (2) Palaeocene/Eocene boundary (Thanetian-Ypresian), (3) Eocene (Ypresian-Lutetian), (4) Eocene-Oligocene (Lutetian-Rupelian), (5) early-late Oligocene (Rupelian-Chattian), (6) early Miocene (Aquitanian-Burdigalian), and (7) middle-late Miocene (Serravallian-Tortonian). These intervals between the hiatuses are correlated with those of the Santos and Campos Basins north from the Pelotas Basin. The breaks in sedimentation that these basins have in common occurred (1) at the Palaeocene-Eocene and (2) Eocene-Oligocene transitions, (3) in the early Miocene, and (4) in the middle-late Miocene. These main unconformities outline five synthems on the SE Brazilian shelf, viz. the SEBS–1 (Palaeocene), SEBS–2 (Eocene), SEBS–3 (Oligocene), SEBS–4 (early-middle Miocene) and SEBS–5 (late Miocene-Holocene). The above unconformities are correlated with those established in the Cenozoic sedimentary successions of different regions such as Western Siberia, Arabia, NW and NE Africa, peninsular India, S Australia, the Gulf of Mexico, NW Europe, and South Africa. The only regional unconformity, near the Oligocene/Miocene boundary, coincides with the nearly-global sedimentation break. The latter was resulted from a climatic event, i.e., the ‘Mi–1 glaciation’. Thus, a eustatic origin is supposed for this regional unconformity. The other regional unconformities also correspond to global sea-level falls (probably with an exception for the Palaeocene/Eocene surface), which suggests that global eustatic movements controlled the development of the regional synthem architecture.
Keywords: synthem; Pelotas Basin; Brazilian continental shelf; Cenozoic